Carbon Dot Therapeutic Platforms: Administration, Distribution, Metabolism, Excretion, Toxicity, and Therapeutic Potential. Issue 16 (27th January 2022) - Truskewycz, Adam; Yin, Hong; Halberg, Nils; Lai, Daniel T. H.; Ball, Andrew S.; Truong, Vi Khanh; Rybicka, Agata Marta; Cole, Ivan
Abstract: Ultrasmall nanoparticles are often grouped under the broad umbrella term of "nanoparticles" when reported in the literature. However, for biomedical applications, their small sizes give them intimate interactions with biological species and endow them with unique functional physiochemical properties. Carbon quantum dots (CQDs) are an emerging class of ultrasmall nanoparticles which have demonstrated considerable biocompatibility and have been employed as potent theragnostic platforms. These particles find application for increasing drug solubility and targeting, along with facilitating the passage of drugs across impermeable membranes (i.e., blood brain barrier). Further functionality can be triggered by various environmental conditions or external stimuli (i.e., pH, temperature, near Infrared (NIR) light, ultrasound), and their intrinsic fluorescence is valuable for diagnostic applications. The focus of this review is to shed light on the therapeutic potential of CQDs and identify how they travel through the body, reach their site of action, administer therapeutic effect, and are excreted. Investigation into their toxicity and compatibility with larger nanoparticle carriers is also examined. The future of CQDs for theragnostic applications is promising due to their multifunctional attributes and documented biocompatibility. As nanomaterial platforms become more commonplace in clinical treatments, the commercialization of CQD therapeutics is anticipated. Abstract : Carbon quantum dots are often grouped under the broad umbrella term of "nanoparticles" when reported in the literature. However, for biomedical applications, their small sizes and unique physiochemical properties give them intimate interactions with biological species. This review investigates their therapeutic potential, passage through the body, how they reach their site of action, administer therapeutic effect, and are excreted.